Chlorin e6-Induced Photodynamic Effect Polarizes the Macrophage Into an M1 Phenotype Through Oxidative DNA Damage and Activation of STING - Yu, Ting-Ting; Han, Ning; Li, Liu-Gen; Peng, Xing-Chun; Li, Qi-Rui; Xu, Hua-Zhen; Wang, Xi-Yong; Yang, Zi-Yi; Chen, Xiao; Wang, Mei-Fang; Li, Tong-Fei (Frontiers in Pharmacology, 2022)
Tumor associated macrophage (TAM) serves as an immunosuppressive agent in the malignant tumor microenvironment, facilitating the development and metastasis of lung cancer. Photodynamic effect destabilizes cellular homeostasis owing to the generation of reactive oxygen species (ROS), resulting in the enhanced pro-inflammatory function of immunocytes. In our previous study, the Ce6-mediated photodynamic effect was found to keep the viability of macrophages and to remodel them into M1 phenotype. However, the mechanism remains unrevealed. The present study now explores the mechanism of photodynamic therapy (PDT) mediated reprogramming of macrophages. As expected, Ce6-mediated PDT was capable of generating ROS, which was continuously degraded, causing "low intensity" damage to DNA and thereby triggering subsequent DNA damage response (DDR) in macrophages. The autophagy was thus observed in Ce6-treated macrophages and was shown to protect cells from being photodynamically apoptosis. More importantly, Ce6 PDT could activate the Stimulator of Interferon Genes (STING) molecule, a sensor of DNA damage, which could activate downstream nuclear factor kappa-B (NF-κB) upon activation, mediating the polarization of macrophages towards the M1 phenotype thereupon. In addition, inhibition of ROS induced by PDT attenuated the DNA damage, STING activation and M1-phenotype reprogramming. Furthermore, the silence of STING weakened Ce6 treatment-mediated M1 remodeling of macrophages as well. Altogether, these findings indicate Ce6 induced photodynamic effect polarizes macrophage into M1 phenotype through oxidative DNA damage and subsequent activation of STING. This work reveals the crucial mechanism by which photodynamic therapy regulates macrophage phenotype, and also provides a novel intervenable signaling target for remodeling macrophages into M1 phenotype.